Understanding field failures of composite insulators. (October 2020) - Nandi, Sounak; Subba Reddy, B.
Highlights: Investigations on composite insulator FRP rod failures reported. A new lab method proposed for FRP rods evaluation. Leakage current, FTIR studies support failure analysis. Comparison of lab and field failure results presented. Abstract: The failure mechanism of in-service fiber reinforced plastic (FRP) rod used in composite insulators is studied experimentally; the integrity of Electrical/Chemical Resistance (ECR) of glass fibers in an epoxy-resin matrix of FRP rod used in transmission composite insulator is the subject of study. FRP Rods are subjected to extreme conditions of aging: the results of leakage current analysis, physical inspection, and corresponding Fourier Transform Infrared Spectroscopy (FTIR) strongly support the reason for the failure of FRP rods under operating condition. The entry of water inside the rod-silicone rubber interface, accompanied by arcing, rise in temperature cause considerable damage and hence failure in the operation of rods. Some interesting results of laboratory aging/failures are compared with field failure samples, also a laboratory method to evaluate failures of FRP rods is proposed.